The Effectiveness of Using the Show and Tell (S&T) Method in Vocabulary Learning Among Seventh-Grade Students at MTs Qamarul Huda Bagu In Academic Year 2024/2025 - Azhari, Hufzon; Wahab, Abdul; Hasbullah, Hasbullah (Tirai Edukasi : Jurnal Pendidikan, 2025)
This study investigates the effectiveness of the Show and Tell (S&T) method in enhancing vocabulary mastery among seventh-grade students at MTs Qomarul Huda Bagu. Employing a quasi-experimental design, the research compared an experimental group taught using the S&T method and a control group taught with conventional methods. Data were collected through pre-tests, post-tests, and classroom observations. The findings revealed that the experimental group showed a significant improvement in vocabulary scores, with a gain score of 20.7 compared to 9.5 in the control group. Statistical analysis confirmed that the difference was significant (t-count = 4.02 > t-table = 2.00, p < 0.05). Observations further indicated that students in the experimental group demonstrated higher participation, confidence, and contextual use of vocabulary. These results suggest that the S&T method is an effective approach to improving vocabulary learning, fostering student-centered, engaging, and meaningful language acquisition